Determinants for the Development of non-Financial Reporting and its External Verification in the Light of Accounting Theory and Practice - Zyznarska-Dworczak, Beata (Studia Oeconomica Posnaniensia, 2017)
The paper presents conclusions from the analysis of factors determining the development of non-financial data measurements included in the performance reports of socially responsible companies. The analysis of developments in non-financial reporting is supplemented by conclusions evaluating the need for its external verification. The analysis was carried out and based on the positive and normative accounting theory. The paper is the result of the author's studies into Polish and foreign source literature as well as her analysis of regulations and standards related to reporting contributions companies make to sustainable development. The paper relies on theoretical triangulation - the issue at hand being identified and the encountered phenomena described and explained by applying the precepts of normative accounting theories, fundamentally based on deductive reasoning, and compared and analysed from the view of positive accounting theories, belonging to the school of induction, describing and explaining the world a posteriori. A synthesis of the conclusions, reached by deduction and induction in particular parts-steps of the paper, enabled to formulate the key findings of the analysis. The paper highlights the need to present both financial and non-financial data when reporting the performance of socially responsible companies so that such data can be verified externally. Conclusions from the analysis of determinants for the development of non-financial reporting and their external independent verification helped anticipate their standardisation and legal regulation.